Study of Epidermal cells, stomatal complex of stems and indumentum of some taxa of the family Amaranthaceae Juus. in Iraq - Feryal K. Khalaf; Athiya N. AL-Mashhadani (Journal of Madenat Alelem University College, 2017)
Current study included important anatomical sites for ten taxa of the family Amaranthaceae. It was covered the anatomical characters of the stems epidermis and the characters of stomatal complex, so the indumentum. The taxa are Alternathera sessilis (L) R. Br. ex De C. Amaranthus albus L, A. caudatus L, A. retroflexu L., A. spinosis L., A. viridis L.,Celosia argentea L.,C. cristata L., Gompharena globosa L., Irisene herbistii Hook.ex Lindl. The results of this study showed that the anatomical characters of the stems epidermis and the indumentum covering different parts of the plant have an important anatomical characters such as the cell wall shape of ordinary epidermal cells also the shape and type of stomata, their presence in some taxa and abscent in others. The hairs also differentiated by their shapes and them types, either they glandular or eglandular also they are different in distribution between the different taxa or in the some taxon.